Reasoned opinion on the dietary risk assessment for proposed temporary maximum residue levels (MRLs) of didecyldimethylammonium chloride (DDAC) and benzalkonium chloride (BAC). (28th April 2014) - ,
Abstract: EFSA was requested by the European Commission to perform a dietary exposure assessment for the proposed temporary maximum residue levels (MRLs) for didecyldimethylammonium chloride (DDAC) and benzalkonium chloride (BAC) (0.1 mg/kg, respectively, for all food commodities covered by the EU MRL legislation). Based on the information, EFSA did not identify potential consumer health risks for these proposed MRLs. Thus, the proposed MRLs are considered to be sufficiently protective. However, due to the limited data available, the risk assessments are affected by a high degree of uncertainty.